2010
DOI: 10.2350/09-03-0632-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

The Number of CD68+ (Hofbauer) Cells is Decreased in Placentas with Chorioamnionitis and with Advancing Gestational Age

Abstract: Hofbauer cells are placental macrophages found in chorionic villous stroma; they express classic monocyte/macrophage markers, such as CD68. Little is known about their participation in placental disease and immunologic interactions at the placental interface. The aim of this study was to quantify the amount of Hofbauer cells in placentas complicated, or not, by chorioamnionitis and in placentas from different gestational ages. Fifty-eight 2nd- and 3rd-trimester placentas with the histologic diagnosis of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
6
27
0
1
Order By: Relevance
“…A similar decrease in CD68 expression also has been reported in CA placentas (50), whereas two studies using a manual count reported an increase in CD68…”
Section: Discussionsupporting
confidence: 75%
“…A similar decrease in CD68 expression also has been reported in CA placentas (50), whereas two studies using a manual count reported an increase in CD68…”
Section: Discussionsupporting
confidence: 75%
“…Because the placenta does not respond in a single way to hypoxia, the histologic changes should be explained in the clinical context and in conjunction with the gross placental and umbilical cord findings. Moreover, because the frequency and degree of expression of many of placental features are qualitatively and/or quantitatively gestational age-dependent, 17,18,57,101,102 for precise evaluation (normal versus abnormal), the criteria presented in Table 1 may be insufficient, and comparison with tables of norms stratified by gestational age may be necessary, but those tables are not, however, available for all hypoxic variables. Such an approach can be helpful not only to better explain cases of perinatal morbidity/mortality and the mechanism of fetal injury, which could potentially be beneficial for management of future pregnancies, but also to help in medicolegal investigation of cases of perinatal morbidity/mortality.…”
Section: Discussionmentioning
confidence: 99%
“…35 They are easily seen in the first and second trimesters, but not in the third trimester (Figure 1, M). A decrease in the amount of CD68 þ cells during second and third trimester is continuous and gradual 17 ( Figure 1, N). Stem obliterative endarteritis, a misnomer term applied to a swelling of intimal cells with occlusion of vascular lumen (Figure 1, O), due to hypoxia-stimulated medial vasoconstriction, is essentially a herniation of smooth muscle cytoplasm into the vascular lumen.…”
mentioning
confidence: 89%
“…Alterations in Hofbauer cell densities within the villi have been reported during chorioamnionitis (106, 107), but there is no evidence that these cells shift to M1 polarity phenotype during chorioamnionitis. Instead, HIV infected Hofbauer cells or cells from chorioamnionitis cases continue to display M2 characteristics such as production of IL-10, TGF-β, expression of DC-SIGN, CD163, and mannose receptor/CD206 (38, 39).…”
Section: Hofbauer Cells In Complicated Pregnancymentioning
confidence: 96%